L’ancienne cité indigène Ruisseau d’Or (actuelle Cité Oued Edheb), une marge urbaine en voie d’intégration à la ville d’Annaba-Algérie - Hadjer Zeghdoudi; Kaddour Boukhemis; Anissa Zeghiche (Belgeo)
The urban margin is a moving socio-spatial entity, modeled by systems of actors, powers and representations evolving in a space-time system. The objective of the paper is not to develop a theoretical reflection on marginality, but to take a look at this question from the ancient indigenous suburb Ruisseau d’Or, a colonial creation on the fringes of the town of Bône, the current Annaba. After a detour through language and history on the meanings and significations of margin, marginal and indigenous city, the emphasis was on the link between the Ruisseau d’Or suburb, material object, and the aims and strategies of existing actors to make and break the margin; and then on the perceptions of the inhabitants of the district; and this thanks to information from archive documents, development and town planning and extensive field work. Our results support the idea that, on the one hand, socio-spatial marginality is neither a coincidence, nor a fate, nor a fixed reality; and on the other hand in the construction of the feeling of satisfaction of the inhabitants, objective reality and the subjective construct are intertwined.